2013
DOI: 10.3109/08958378.2013.768314
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation dosimetry of hexamethylene diisocyanate vapor in the rat and human respiratory tracts

Abstract: Hexamethylene diisocyanate (HDI) is a reactive chemical used in the commercial production of polyurethanes. Toxic effects in rodents exposed to HDI vapor primarily occur in the nasal passages, yet some individuals exposed occupationally to concentrations exceeding current regulatory limits may experience temporary reduction in lung function and asthma-like symptoms. Knowledge of interspecies differences in respiratory tract dosimetry of inhaled HDI would improve our understanding of human health risks to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The protocols applied focused on the analysis of the concentration × time ( C × t )–response relationship on elicitation-based endpoints by employing a highly rationalized dose-escalation-like protocol. For the HDI-vapor, a C const × t var regimen was selected with a “ C” high enough to overcome the scrubbing capacity of the nasal passages of the obligate nasal breathing rats (Schroeter et al., 2013 ; Shiotsuka et al., 2006 , 2010 ). Ancillary pre-studies served the purpose of identifying that “ C ” of HDI-vapor gains access to the lower airways at stable breathing conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocols applied focused on the analysis of the concentration × time ( C × t )–response relationship on elicitation-based endpoints by employing a highly rationalized dose-escalation-like protocol. For the HDI-vapor, a C const × t var regimen was selected with a “ C” high enough to overcome the scrubbing capacity of the nasal passages of the obligate nasal breathing rats (Schroeter et al., 2013 ; Shiotsuka et al., 2006 , 2010 ). Ancillary pre-studies served the purpose of identifying that “ C ” of HDI-vapor gains access to the lower airways at stable breathing conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The workday and ppmV-adjusted equivalent were estimated to be 23 (mg/m 3 × min) × 1/7 (conversion from mg to ppmV) × 1/480 min −1 = 0.007 ppmV. The derivation of the rat to human conversion factor assumed that bronchial airways of oronasally breathing humans are subjected to a 3-times higher dose as compared with nasally breathing rats (Schroeter et al., 2013 ). Likewise, due to the reflexively-induced depression of ventilation occurring in rats, the inhaled dose of rats exposed to HDI-vapor at concentrations penetrating the lower respiratory tract is likely to be about one-third of normally breathing rats.…”
Section: Methodsmentioning
confidence: 99%
“…An in silico model, such as the Multiple Path Particle Dosimetry Model (MPPD) is a wellestablished, validated, and accepted model that can help identify the location of a particular droplet/particle size is expected to reach and deposit and where lesions of cellular damage may occur. [61][62][63][64][65] A mass per unit surface area can then be applied to both in vivo (which has been done successfully for validation purposes) and in vitro applications for establishing the appropriate droplet/particle size to emulate the intended exposure scenario that investigators wish to assess for potential exposure effects.…”
Section: Test Bed System For Immunotoxicological Responsesmentioning
confidence: 99%
“…Animal studies of HDI exposure to identify “self” reaction targets in the lower airway have been compromised by inherent species differences with humans; for example, rodents are obligate nose breathers and their upper airways are proportionally larger and possess a scrubbing effect or capacity for absorbing/capturing reactive vapors (Ferguson et al, 1988; Harkema et al, 2006; Kennedy et al, 1993; Morris & Buckpitt, 2009; Schroeter et al, 2013). Prior rat and guinea pig studies with several different radiolabeled monoand di-isocyanates demonstrated limited penetration into the lower airways and higher levels of upper airway and oral absorption (Ferguson et al, 1988; Gledhill et al, 2005; Kennedy et al, 1994; Schroeter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Prior rat and guinea pig studies with several different radiolabeled monoand di-isocyanates demonstrated limited penetration into the lower airways and higher levels of upper airway and oral absorption (Ferguson et al, 1988; Gledhill et al, 2005; Kennedy et al, 1994; Schroeter et al, 2013). …”
Section: Introductionmentioning
confidence: 99%